INTERSTELLAR MOLECULAR LINES IN A STARS - PEIMBERT, M (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1965)
Seven A and two B9 stars near the galactic plane were observed spectroscopically in the blue region. Two of these stars and possibly a third one show interstellar lines of CN. From the CN lines of HR 618 an excitation temperature T_E = 3.7 +/- 0.7°K was d
BOL OBS TONAN TACUB
Keywords: INTERSTELLAR, MOLECULAR, LINES, STARS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS